The leading factors of street teenagers' risky sexual behavior - Anindhita Setianingrum; Zahroh Shaluhiyah; Bagoes Widjanarko (Alma Ata University Press, 2022)
Background: Teenagers who live on the streets are groups in a society prone to sexual violence and reproductive health risks. Sexually active street teenagers often engage in sexual activity in any place, change partners, and do not use contraceptives to prevent pregnancy and the risk of sexually transmitted diseases. Objective: This study aimed to analyze factors related to risky sexual behavior of street teenagers in Semarang. Methods: This study used a cross-sectional design with a research population of 10-18 years old street teenagers who became street teenagers assisted by the Social Office of Semarang. A sample of 81 teenagers was selected using the total population sampling technique. Data analysis used the Chi-square test and logistic regression with the 95% confidence level. Results: The study results found a significant correlation between age, parental status, permissive attitude, risky health behavior, friends’ attitude, and friends’ risky reproductive health behavior with the risky sexual behavior of street teenagers in Semarang City (p<0.05). Multivariate analysis showed that the variables of friends’ attitudes and friends’ risky behaviors had simultaneous effects on street teenagers’ risky sexual behavior. Street teenagers who had friends with permissive attitudes were more at risk of engaging in sexual behavior 13 times than those who did not have permissive friends. Street teenagers who had friends with high-risk sexual behaviors were also ten times more likely to have risky sexual behaviors than those who had friends with low-risk behaviors.Conclusion: This study concluded that the variable of friends’ attitude had the most significant influence on risky sexual behavior of street teenagers in Semarang. The efforts were necessary to establish peer-educators related to reproductive health education for street teenagers to reduce reproductive health risks.